Screen Indians in the EFL-Classroom: Transnational Perspectives - Karsten Fitz (American Studies Journal, 2008)
This article addresses the question of what different audiences ‘see’ when watching movies depicting Native Americans, arguing that ways of ‘seeing’ are deeply embedded in specific cultural contexts. In particular, it is concerned with what a German movie-going audience—our EFL-students, in particular—see when watching blockbuster Hollywood movies like Dances with Wolves or popular Native American productions like Smoke Signals? Against the background of the West German Winnetou films and the East German DEFA westerns, respectively, German audiences on both sides of the iron curtain have been appropriating ‘Indians’ on their own terms, ‘using’ them for their own purposes and within their own cultural frames of reference.